2008
DOI: 10.1007/s10096-007-0449-3
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-susceptible, non-multiresistant methicillin-resistant and multiresistant methicillin-resistant Staphylococcus aureus infections: a clinical, epidemiological and microbiological comparative study

Abstract: Non-multiresistant methicillin-resistant Staphylococcus aureus (nmMRSA) infections are emerging worldwide and are often community-associated. This prospective case-cohort study compares features of 96 nmMRSA clinical isolates with 96 matched multiresistant MRSA (mMRSA) and 192 matched methicillin-susceptible S. aureus (MSSA) clinical isolates. Seventy-four percent of nmMRSA infections were healthcare-associated. nmMRSA infections were much more likely to involve skin and soft tissue (skin and soft tissue infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
3
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 41 publications
7
56
3
1
Order By: Relevance
“…Altogether, these data suggest that the PVLs produced by each CA-MRSA and MSSA lineage are equally leukotoxic. This in vitro observation is in accordance with clinical observations that PVLs impact on the severity of human skin and soft tissue infections, necrotizing pneumonia, and bone and joint infections regardless of the genetic background and the mecA status of the isolated strains (3,11,20).…”
Section: Discussionsupporting
confidence: 90%
“…Altogether, these data suggest that the PVLs produced by each CA-MRSA and MSSA lineage are equally leukotoxic. This in vitro observation is in accordance with clinical observations that PVLs impact on the severity of human skin and soft tissue infections, necrotizing pneumonia, and bone and joint infections regardless of the genetic background and the mecA status of the isolated strains (3,11,20).…”
Section: Discussionsupporting
confidence: 90%
“…CC/ST59-MRSA-V is among the predominant CA-MRSA clones in some northern European countries (21). In contrast, similar to in the present study, ST93-MRSA-IV has only been reported sporadically in Europe (21,53) but is the dominant pvl-positive MRSA strain in Australia, where it has spread into health care facilities (54). Increasing reports of outbreaks of pvl-positive MRSA, particularly in NICUs, highlights the ability of these strains to spread among vulnerable patient groups in hospitals (24,25,47,48).…”
Section: A Total Of 229supporting
confidence: 82%
“…However, other studies that used a methodology similar to that of our study reported much lower prevalence rates, ranging from 7 to 12% (13,21,29). In Auckland, PVL-positive MSSA was strongly associated with the diagnosis of SSTI; 48% of all MSSA isolates associated with SSTI were lukSF-PV positive.…”
Section: Discussionmentioning
confidence: 37%